Morphology of electrospun PVA nanofibers enhanced with graphene oxide, Poly (3,4 ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), and multiwalled carbon nanotubes - Ahmad Shahizam, Zayd (Scientific Institute for Advanced Training and Studies, 2020)
Morphology of poly(vinyl alcohol) (PVA) nanofibers was studied while varying needle-collector distance and concentrations of graphene oxide, poly (3,4-ethylenedioxythiophene):polystyrene sulfonate (PEDOT:PSS), and functionalized multiwalled carbon nanotubes. Most notably, we found that variations in PVA nanofiber diameter of ~ 34 nm exist in the radial area of electrospinning; the variation is believed to be the result of a fringing electric field effect at the edge of the collector plates. Needle-collector distance was varied between 10 and 17 cm, and FESEM images revealed average fiber diameter decreased from 173 nm to 144 nm with no obvious change in morphology at both nanofiber diameters. Similarly, electrospinning of PVA-GO solution at 17 cm resulted in nanofibers with decreased average diameter of 197 nm (σ = 97 nm), compared with PVA alone (349 nm, σ = 87 nm) with no obvious change in morphology. The average diameter of PVA nanofibers then increased with added PEDOT:PSS to 244 nm, σ = 75 nm. PVA-MWCNT samples at 2 wt% and 4 wt% showed no beading, while at 6, 8, and 10 wt%, beads were prevalent in the fibers. The presence of beads could be the result of re-agglomeration of MWCNTs in the electrospinning solution at higher wt%. No clear trend was found with increasing concentrations of MWCNTs, with average nanofiber diameters varying in the range of 115 – 206 nm.